Summer Pruning in Low-Chill Peaches Grown in Florida - Ali Sarkhosh; Dustin Huff; Trequan McGee; Juanita Popenoe (EDIS)
Low-chill peach trees growing under Florida conditions can become vigorous and large. Summer pruning is a management strategy that can be applied to help restructure the canopy, direct the tree’s resources into fruit production, and improve the efficiency of fieldwork. Without summer pruning, peach orchards in subtropical regions will continue to grow vigorously and, if left unmanaged, will reach a point at which ladders will be required to harvest and maintain the trees. Summer pruning can be a means of reducing overall tree size, redistributing fruiting wood for easier harvesting, reducing disease pressure, and increasing fruit quality. This new 5-page publication of the UF/IFAS Horticultural Sciences Department, written by Ali Sarkhosh, Dustin Huff, Trequan McGee, and Juanita Popenoe, provides an illustrated step-by-step guide to summer pruning of peach trees. https://edis.ifas.ufl.edu/hs1377